Characterization of Structural and Electrochromic Properties of Nanocomposite \(\text{TiO}_{2}-\text{WO}_{3} \) Films - Ninh, Dang Hai; Thao, Tran Thi; Dinh, Nguyen Nang; Long, Pham Duy (Communications in Physics, 2014)
Using doctor-blade technique, followed by electrochemical deposition, nanocomposite WO\(_{3}\)-TiO\(_{2}\) films were prepared. Structure, morphology and composition ratio of the nanocomposite films were characterized by a comprehensive analyzing the SEM, EDX, XRD and Raman scattering results. The reversible coloration and bleaching of TiO\(_{2}\)/ITO and WO\(_{3}\)-TiO\(_{2}\)/ITO electrodes were demonstrated. The ECD coloration efficiency of WO\(_{3}\)-TiO\(_{2}\)/ITO was found to be much larger (55.1 cm\(^{2}× \text{C}^{ - 1})\) than that of TiO\(_{2}\)/ITO (34.3 cm\(^{2}× \text{C}^{ - 1})\). The resulting nanostructured composites enables the coloration efficiency of the WO\(_{3}\)-TiO\(_{2}\) film to be considerably improved. The results suggest a potential application of the nanocomposites of two electrochromic oxides in large-area energy-efficiency (or smart) windows.